Involvement of the Undergraduate Accounting Curriculum with Distribution Cost Analysis. - Hise, Richard T.; Kratchman, Stanley H.; Mattheiss, Theodore H. (The Accounting Review, 1974)
Presents information on a study which examined undergraduate accounting curriculum with distribution cost analysis. Analysis of undergraduate accounting curricula; Results and discussion.